2009
DOI: 10.1002/ijc.24428
|View full text |Cite
|
Sign up to set email alerts
|

P21‐activated kinase 5 is overexpressed during colorectal cancer progression and regulates colorectal carcinoma cell adhesion and migration

Abstract: P21-activated kinase 5 (PAK5) is the recently identified member of the group B p21-activated kinase (PAK) family which are effectors of the small GTPase Cdc42 and Rac1, known to regulate cell motility and activate cell-survival signaling pathways. However, overexpression of PAK5 has not been associated with any cancers so far. Interestingly, we found that PAK5 was overexpressed in a variety of colorectal carcinoma (CRC) cell lines in a Western-blotting examination. Therefore, in this study, we aim to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 36 publications
1
55
1
Order By: Relevance
“…Moreover we find differential levels of PAK5 mRNA expression in human normal bladder tissue compared to carcinoma samples. Our findings are not in agreement with some previous reports that suggest PAK5 expression increases with malignant disease in colorectal 60,61 , gastric 62 and hepatocellular carcinoma 63 . However, on reviewing these publications, the sensitivity and specificity antibodies used to detect PAK5…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover we find differential levels of PAK5 mRNA expression in human normal bladder tissue compared to carcinoma samples. Our findings are not in agreement with some previous reports that suggest PAK5 expression increases with malignant disease in colorectal 60,61 , gastric 62 and hepatocellular carcinoma 63 . However, on reviewing these publications, the sensitivity and specificity antibodies used to detect PAK5…”
contrasting
confidence: 99%
“…For example in the colorectal study 61 , the isoform specificity of the polyclonal antibody has not been well described. The epitope for antibody recognition was generated against 224-amino acids N-terminal sequence of PAK5, and cross reaction with PAK4 was excluded.…”
mentioning
confidence: 99%
“…PAK4 is closely associated with the progression and metastasis of breast cancer [32] , the adhesion of prostate cancer cells [33] and the migration of human gastric cancer cells [34] , and PAK6 is overexpressed in prostate cancer and breast cancer cell lines [29,35] . Several studies have provided detailed insights into the role of the PAK5 protein in colorectal cancer [15,16] and pancreatic [17] . However, the role of PAK5 in HCC tumorigenesis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The other members of the PAK family have been identified as regulators of tumor formation in the breast [10] , colon [11] , ovary [12] , pancreas [13] , and prostate [14] . Although the role of PAK5 in cancer progression has not been fully investigated, two recent reports suggest that PAK5 is overexpressed in colorectal cancer and can promote cancer-cell invasion [15,16] . Furthermore, the combined inhibition of PAK7, MAP3K7, and CK2a kinases was shown to inhibit the growth of MiaPaCa2 pancreatic cancer cell xenografts [17] .…”
Section: Wwwchinapharcom Fang Zp Et Almentioning
confidence: 99%
“…The role of PAK5 in various types of cancer has been investigated by several groups. Inhibiting PAK5 expression induced a 7-fold increase in apoptosis in the pancreatic adenocarcinoma cell line MiaPaCa-2, suggesting that PAK5 is a kinase that may protect pancreatic cancer cells from apoptosis (11) PAK5 overexpression assessed using immunohistochemistry was reported in certain colorectal cancer types, and PAK5 reduced colorectal carcinoma cell adhesion; however PAK5 promoted cellular migration on collagen type I, indicating that PAK5 is involved in colorectal cancer cell migration and invasion (12). Immunohistochemical analysis demonstrated that PAK5 expression was upregulated significantly in different gastric cancer cell lines and gastric cancer tissue samples, as compared with human embryonic kidney 293 cells and adjacent normal tissue samples (13).…”
Section: Introductionmentioning
confidence: 99%